A Three‐Component Enantioselective Cyclization Reaction Catalyzed by an Unnatural Amino Acid Derivative. (12th December 2017) - de Gracia Retamosa, María; Ruiz‐Olalla, Andrea; Bello, Tamara; de Cózar, Abel; Cossío, Fernando P.
Abstract: A new diastereo‐ and enantioselective three‐component cyclization reaction is described. The reaction takes place between a ketone, a carboxylic acid, and a nitroalkene to yield a bicyclic octahydro‐2 H ‐indol‐2‐one scaffold possessing three chiral centers. This reaction involves a rearrangement of the nitro group under simple thermal conditions. A plausible mechanism is proposed for this new reaction based on DFT calculations and isotope‐labeling experiments. A new concise enantioselective synthesis of the alkaloid (+)‐pancracine is presented as an example of the potential of this novel organocatalytic cyclization reaction in the synthesis of natural products.